Correlation Between Objective and Subjective High-Pitched Voice Impairment in Patients After Thyroid Surgery - Huang, Tzu-Yen; Yu, Wing-Hei Viola; Chiang, Feng-Yu; Wu, Che-Wei; Fu, Shih-Chen; Tai, An-Shun; Lin, Yi-Chu; Tseng, Hsin-Yi; Lee, Ka-Wo; Lin, Sheng-Hsuan (Frontiers in Endocrinology, 2021)
Objectives: High-pitched voice impairment (HPVI) is not uncommon in patients without recurrent laryngeal nerve (RLN) or external branch of superior laryngeal nerve (EBSLN) injury after thyroidectomy. This study evaluated the correlation between subjective and objective HPVI in patients after thyroid surgery. Methods: This study analyzed 775 patients without preoperative subjective HPVI and underwent neuromonitored thyroidectomy with normal RLN/EBSLN function. Multi-dimensional voice program, voice range profile and Index of voice and swallowing handicap of thyroidectomy (IVST) were performed during the preoperative(I) period and the immediate(II), short-term(III) and long-term(IV) postoperative periods. The severity of objective HPVI was categorized into four groups according to the decrease in maximum frequency (Fmax): <20%, 20-40%, 40-60%, and >60%. Subjective HPVI was evaluated according to the patient’s answers on the IVST. Results: As the severity of objective HPVI increased, patients were significantly more to receive bilateral surgery (p=0.002) and have subjective HPVI (p<0.001), and there was no correlation with IVST scores. Among 211(27.2%) patients with subjective HPVI, patients were significantly more to receive bilateral surgery(p=0.003) and central neck dissection(p<0.001). These patients had very similar trends for Fmax, pitch range, and mean fundamental frequency as patients with 20-40% Fmax decrease(p>0.05) and had higher Jitter, Shimmer, and IVST scores than patients in any of the objective HPVI groups; subjective HPVI lasted until period-IV. Conclusion: The factors that affect a patient's subjective HPVI are complex, and voice stability (Jitter and Shimmer) is no less important than the Fmax level. When patients have subjective HPVI without a significant Fmax decrease after thyroid surgery, abnormal voice stability should be considered and managed. Fmax and IVST scores should be interpreted comprehensively, and surgeons and speech-language pathologists should work together to identify patients with HPVI early and arrange speech therapy for them. Regarding the process of fibrosis formation, anti-adhesive material application and postoperative intervention for HPVI require more future research.